Why art? Exploring the contribution to mental well-being of the creative aspects and processes of visual art-making in an arts and mental health course. Issue 1 (2nd January 2018) - Secker, Jenny; Heydinrych, Kirsten; Kent, Lyn; Keay, Jo
Abstract: Background: Evaluations of participatory arts and mental health projects have consistently found improvements in mental well-being but the part played by the creative aspects, as distinct from the benefits of social interaction, remains unclear. Methods: This study explored the specific part played by the creative aspects of introductory arts courses that aim to improve mental well-being. Nine course participants consented to recording of accreditation assessment meetings held with them towards the end of their course. Results: Thematic analysis identified themes relating to two categories: creative processes and the learning that ensued. The creative processes were playful experimentation and inspiration. Learning processes revolved around learning to learn and artistic development. Conclusions: Previous studies have found play, inspiration and learning to be associated with well-being. It therefore seems reasonable to conclude that the creative aspects of the courses did play an important part in improving participants' well-being.